[Solid Lead Dancers, Rose Float - Breakin' the Ice, Fire at Engineering West]
[00:00:00] An MC introduces the Solid Lead Dancers, a comedy dance group [00:00:55] Dancers introduced, begin dancing to top hits of 1986 [00:04:52] View of Breakin' the ice rose float mascot penguin on pickup truck with skateboarders trailing behind [00:06:35] View of fire in engineering west building as people crowd the street to watch